2019
DOI: 10.1002/ana.25611
|View full text |Cite
|
Sign up to set email alerts
|

Duration of American Football Play and Chronic Traumatic Encephalopathy

Abstract: Objective Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease associated with exposure to contact and collision sports, including American football. We hypothesized a dose–response relationship between duration of football played and CTE risk and severity. Methods In a convenience sample of 266 deceased American football players from the Veterans Affairs–Boston University–Concussion Legacy Foundation and Framingham Heart Study Brain Banks, we estimated the association of years of football pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
178
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 177 publications
(193 citation statements)
references
References 46 publications
9
178
4
2
Order By: Relevance
“…Studying the same sample, [30] reported that exposure to football before age 12 was associated with increased odds of cognitive and neuropsychiatric impairment. A more recent study [31] of the same sample, however, found that age of first exposure was not associated with CTE pathology. These studies are limited by the use of volunteer participants and their retrospective design.…”
Section: Background and Motivationmentioning
confidence: 70%
“…Studying the same sample, [30] reported that exposure to football before age 12 was associated with increased odds of cognitive and neuropsychiatric impairment. A more recent study [31] of the same sample, however, found that age of first exposure was not associated with CTE pathology. These studies are limited by the use of volunteer participants and their retrospective design.…”
Section: Background and Motivationmentioning
confidence: 70%
“…Among former amateur and professional football players, the risk of developing CTE, which is associated with dementia, increases 30% per year played. 175 Currently, there is no test to determine if someone has CTE-related brain changes during life. A review article indicates that the greatest risk factor for developing CTE-related brain changes is repetitive brain trauma -repeated, forceful blows to the head that do not, individually, result in symptoms.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
“…Although research from the UNITE study has identified an association between American football play and CTE, the strength of this relationship was only recently quantified among 266 deceased male American football players from the VA-BU-CLF (n ¼ 255) and Framingham Heart Study Brain Banks (n ¼ 11). 33 Of the sample 223 had CTE and 43 did not. The odds of CTE increased by 30% for each additional year played.…”
Section: Neuropathological Evidencementioning
confidence: 99%